Deskripsi Kemampuan Berpikir Tingkat Tinggi Siswa Kelas XI IPA SMA dalam Menyelesaikan Soal Program Linear ditinjau dari Kecerdasan Adversitas dan Efikasi Diri - Juwita Sari; Nasrullah; Usman Ulbar (Issues in Mathematics Education (IMED), 2020)
The aim of this research is to determine the general description of students' adversity quotient and self-efficacy from grade XI IPA and finding out how the description of students higher order thinking skills in solving linear program problems viewed from students’ adversity quotient and self-efficacy. The type of this research is descriptive research with mixed method approach. The subjects of this research were 4 students, those are 1 students has high self-efficacy-climbers, 1 students has low self-efficacy-climbers, 1 students has high self-efficacy-campers, and 1 students has low self-efficacy-campers. The research instrument used consist of ARP questionnaire (Adversity Response Profile), self-efficacy questionnaire, higher order thinking skills test of linear program and interview guidelines. The results of the research showed that: (1) The most of students (70%) had high self-efficacy. (2) The most of students (86,5%) had campers adversity quotient. (3) Students who had high self-efficacy-climbers was able to fulfill three indicators of higher order thinking skills. (4) Students who had low self-efficacy-climbers was able to fulfill two indicators of higher order thinking skills, i.e analyzing and evaluating. (5) Students who had high self-efficacy-campers was able to fulfill two indicators of higher order thinking skills, i.e analyzing and evaluating. (6) Students who had low self-efficacy-campers was not able to fulfill all indicators of higher order thinking skills.